Decadal-scale trends in regional aerosol particle properties and their linkage to emission changes. (19th May 2017) - Zhao, Bin; Jiang, Jonathan H; Gu, Yu; Diner, David; Worden, John; Liou, Kuo-Nan; Su, Hui; Xing, Jia; Garay, Michael; Huang, Lei
Abstract: Understanding long-term trends in aerosol loading and properties is essential for evaluating the health and climatic effects of these airborne particulates as well as the effectiveness of pollution control policies. While many studies have used satellite data to examine the trends in aerosol optical depth (AOD), very few have investigated the trends in aerosol properties associated with particle size, morphology, and light absorption. In this study, we investigate decadal-scale (13–15 year) trends in aerosol loading and properties during 2001–2015 over three populous regions: the Eastern United States (EUS), Western Europe (WEU), and Eastern and Central China (ECC). We use observations from MISR (Multi-angle Imaging SpectroRadiometer) and MODIS (Moderate resolution Imaging Spectroradiometer). Relationships between aerosol property trends and air pollutant emission changes are examined. We find that annual mean AOD shows pronounced decreasing trends over EUS and WEU regions, as a result of considerable emission reductions in all major pollutants except for mineral dust and ammonia (NH3 ). Over the ECC region, AOD increases before 2006 due to emission increases induced by rapid economic development, fluctuates between 2006 and 2011, and subsequently decreases after 2011 in conjunction with effective emission reduction in anthropogenic primary aerosols, sulfur dioxide (SO2 ), and nitrogen oxides (NOx ). The fraction of small-size AOD (<0.7  μ m diameter), Ångstrom exponent and single-scattering albedo have generally decreased, while the fractions of large-size (>1.4 μ m diameter), nonspherical and absorbing AOD have generally shown increasing trends over EUS and WEU regions, indicating that fine and light-scattering aerosol constituents have been more effectively reduced than coarse and light-absorbing constituents. These trends are consistent with the larger reduction ratios in SO2 and NOx emissions than in primary aerosols, including mineral dust and black carbon (BC). Over the ECC region, no significant trends are observed with respect to size distribution, morphology, or light absorption, which we attribute to a simultaneous increase in emissions of SO2, NOx, and primary aerosols including BC before 2006, and a simultaneous decrease after 2011. This study demonstrates the importance and usefulness of satellite-borne sensors, particularly MISR, in association with evaluating the effectiveness of air pollution control policies.